Effects of soil reinforcement on seismic performance of low-to-medium rise buildings - Akçay, Yusuf Ali. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2021., 2021)
Soil reinforcement is used to improve the stiffness and strength of soil. The benefits of reinforcement inclusions within soil mass to increase the bearing capacity and reduce the settlement of soil foundation have been widely studied. The principle of geosynthetic reinforced soil method briefly is to deploy horizontal layers of closely spaced tensile inclusion in the fill material to achieve stability of a soil mass. This study aimed to determine the applicability and effectiveness of a proposed geogrid reinforcement system for low-rise and mid-rise buildings under earthquake loadings to mitigate earthquake effects. In order to observe the effectiveness of the proposed reinforcement system, a set of shaking table experiments were carried out with and without soil reinforcement. To determine structure and soil behavior together, an experimental set-up was desgined. The effects of the number of the story, the number of geogrids layers and ground motion characteristic were evaluated and the effects of all these parameters on system were investigated. There are many experimental studies showing that the ratio of geogrid length (L) to building foundation width (B) affects experimental results under static loads. In this study, the L/B ratio was taken as 2.3. This value is the highest possible L/B ratio due to limitations in the experimental setup. When the results of experiments are evaluated, it is clearly seen that proposed reinforcement system can reduce the horizontal accelerations, horizontal drifts in the soil, story displacement of the building. The seismic energy transmitted from ground to the structure without geogrid reinforcement system in the soil can be decreased through this system. Therefore, proposed geogrid reinforcement system can be used to improve the seismic resistance capacity of the structures against strong ground motions.
Keywords: Soil remediation.; Geosynthetics.